The Russian Novel, Literature 5113.88. - Dade County Public Schools, Miami, FL.; Dade County Public Schools, Miami, FL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Developed for a high school quinmester unit on the Russian novel, this guide is designed to give students the opportunity to become familiar with the major works of Leo Tolstoy and Fyodor Dostoevski. Performance objectives for the course include studying the general facets of 19th century Russian culture and history, analyzing the novels of Dostoevski and Tolstoy to note elements of similarity and difference, and contrasting the works of Dostoevski and Tolstoy with a variety of works by other Russian writers. Also included are "Course Content," which provides a rationale for the course and a list of subject matter range; "Teaching Strategies," which suggests activities, techniques, and instructional materials; and "Student and Teacher Resources," which lists state-adopted textbooks, nonstate-adopted textbooks, reference materials, and films for use in teaching the Russian novel. (RB)
ERIC Note: Authorized course of instruction for the Quinmester Program.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Course Content; Course Descriptions; English Instruction; Instructional Materials; Language Arts; Literary Criticism; Minicourses; Novels; Russian Literature; Secondary Education; Teaching Guides; Quinmester Program; Guides, General